Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1073/pnas.88.1.234
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of cDNA encoding the enzyme that controls conversion of high-mannose to hybrid and complex N-glycans: UDP-N-acetylglucosamine: alpha-3-D-mannoside beta-1,2-N-acetylglucosaminyltransferase I.

Abstract: UDP-GlcNAc:a-3-D-mannoside P-1,2-Nacetylglucosaminyltransferase I (GnT I; EC 2.4.1.101) catalyzes an essential first step in the conversion of high-mannose N-glycans to hybrid and complex N-glycans. Cloning of the gene encoding this enzyme was carried out by mixed ollgonucleotide-primed polymerase chain reaction amplification of rabbit liver single-stranded cDNA using sense and antisense 20-to 24-base-pair (bp) primers. A rabbit liver library in phage AgtlO yielded a 2.5-kilobase (kb) cDNA with a 447-amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(33 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…Besides the cDNA isolated in the present study, cDNA has been obtained for only one other GlcNAc transferase (30,31). Although these enzymes utilize the same nucleotide sugar, UDP-GlcNAc, no homology in primary amino acid sequence could be detected between these two enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the cDNA isolated in the present study, cDNA has been obtained for only one other GlcNAc transferase (30,31). Although these enzymes utilize the same nucleotide sugar, UDP-GlcNAc, no homology in primary amino acid sequence could be detected between these two enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the primary sequences of GT revealed that the entire transmembrane domain is identical in human and bovine and that 19 of the 20 residues in the transmembrane domain are also conserved in mouse (DAgostaro et al ., 1989 ;Masri et al ., 1988 ;Russo et al ., 1990 ;Shaper et al, 1988). Furthermore, the sequence of the transmembrane domain of NTI is totally conserved between human and rabbit (Kumar et al ., 1990 ;Sarkar et al ., 1991). The high degree of conser-…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sequence comparison with glycosyltransferases cloned by others, including ~-l,2-N-acetylglucosaminyltransferase I (Kumar et al 1990;Sarkar et al 1991) and f3-1,4- 5B, C). However, the homology in the amino acid sequences of this portion is not as long as the aforementioned.…”
Section: Ignt and C2gnt Are Homologous To Each Othermentioning
confidence: 99%